2005
DOI: 10.1379/csc-74r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia on stress proteins in the piglet heart at birth

Abstract: Hypoxia at birth represents a very stressful event that can result in severe lifelong consequences in different tissues, including those of the heart. Heat shock and other associated stress proteins are involved in cellular protection, but their roles are not clearly defined at the time of birth. Newborn piglets were subjected to 5% oxygen and 95% nitrogen for either 1 or 4 hours. They were allowed to recover over periods of 1 to 68 hours. The relative levels of ␣B-crystallin, HspB8, Hsp20, Hsp27, Hsp60, and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
2
33
0
2
Order By: Relevance
“…12 ␣B-crystallin expression is up-regulated during in vitro angiogenesis 17 and is increased in heart tissues undergoing hypoxia. 15 We recently showed that after chemical hypoxia, ␣B-crystallin demonstrated an initial increase in expression followed by down-regulation at later time points. 16 These results suggest that the effect of hypoxia on expression of ␣B-crystallin varies in different cell types and types of hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 ␣B-crystallin expression is up-regulated during in vitro angiogenesis 17 and is increased in heart tissues undergoing hypoxia. 15 We recently showed that after chemical hypoxia, ␣B-crystallin demonstrated an initial increase in expression followed by down-regulation at later time points. 16 These results suggest that the effect of hypoxia on expression of ␣B-crystallin varies in different cell types and types of hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition to being a molecular chaperone, ␣B-crystallin functions in apoptosis inhibition, cellular protection, and proteasomal interactions. 12,14 It was recently shown that ␣B-crystallin expression was modulated by hypoxia 15,16 and regulates tumor angiogenesis 17 ; however, little is known about the mechanistic role of ␣B-crystallin in angiogenesis. The aim of this study was to investigate vascular pathology of ␣B-crystallin Ϫ/Ϫ and wild-type mice in 2 distinct models of intraocular neovascularization, with particular emphasis on VEGF-A mRNA and protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile to mention that expression of different small heat shock protein is tissue-specific and is also dependent on the physiological stage. However, on the average, the levels of HspB1 and HspB5 expression are comparable, exceeding by up two times the level of HspB6 and by up to four times the levels of HspB8, respectively (Kato et al 1992(Kato et al , 1994Louapre et al 2005;Verschuure et al 2003;Huey et al 2004). This fact together with the low probability of subunit exchange makes participation of HspB8 in the formation of heterooligomeric complexes with other small heat shock proteins rather improbable.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in newborn piglets that have been subjected to hypoxiaischemia in laboratory experiments, modified expression patterns of stress related proteins have been demonstrated in brain, heart and intestines [5][6][7]. Apparently this attributes to clinical signs, varying from www.theriojournal.com delivery of less viable piglets [1,2] and reduced early postnatal vitality [2,3] to decreased growth and survival rates until the age of 10 days [3].…”
Section: Introductionmentioning
confidence: 99%